A agricultura familiar e suas múltiplas interaç\~oes com o território: Una análise de suas características multifuncionais e pluriativas - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This work analyzes the main aspects pluriactive and multifunctional agriculture involving familiar with the territorial dynamics of larger scale, according to regional characteristics under which they operate. It is understood that the notion of multifunctionality analyze the interaction between families and territories in the dynamics of social reproduction, including also the generation of a number of public and private goods. It enhances an essential dimension of the relationship between family farmers and territory, which is its inter-sector, while agriculture remains as relevant economic sector. This intersectoral character also is not just the productive sectors, because while family units, they require a number of public and private services, which makes their social reproduction of family farming generates a lot of opportunities to boost the local economic environment. The rural is no longer seen only as a space for agricultural production and is seen as a macro-social organism, complex and strongly overlapping the territory through its labor relations, production and consumption.
Keywords: Q18; Q56; 330; multifunctionality; pluriativity; family farming; territory; land reform